Lepidopteros-praga associados com estágios fenológicos de cultivares de soja - Carneiro, Eliane; Silva, Luciana Barboza; da Silva, Alexandre Faria; Lopes, Gleidyane Novais; Pavan, Bruno Ettore [UNESP]; Rodrigues, Raimundo Henrique Ferreira; Carvalhinho, Diego Tavares; Mielezrski, Diego Fabio (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2018)
Lepidopteran pests are one of the major constraints to the soybean production potential, whose defoliating caterpillars can occur throughout the crop cycle causing serious damage. Therefore, the objective was to study the population fluctuation of lepidopteran pests and the association of species with the growth stages of soybean cultivars in the Cerrado of Piaui State, Brazil, in order to obtain data to support integrated pest management in the crop. The experiments had as a source of variation thirteen cultivars with fourteen evaluations. The design used was completely randomized in split plots being the cultivars plots and subplots the cultivars phenological stages. The monitoring was conducted by shake-cloth method at random points. Weekly samplings were performed. Generally, species of lepidopteran pests occurred in all soybean phenological stages, especially Chrysodeixis includens and Anticarsia gemmatalis that were present from the beginning to the end of the crop.
Lepidopteran pests associated with the soybean cultivars phenology
Keywords: Infestation; Integrated pest management; Monitoring